HEPATITIS B VIRUS INFECTED INDIVIDUALS' QUALITY OF LIFE AND RELATED FACTORS - Ummi Maimunah; Ulfa Kholili; Amie Vidyani; Annisa Zahra Mufida; Diah Rizki Rahma Dini; Isna Mahmudah; Titong Sugiharto; Muhammad Miftahussurur (Ikatan Dosen Menulis, 2024)
Globally, hepatitis B is a public health issue, and Indonesia is not an exception. We investigated a number of factors related to chronic hepatitis B patients' quality of life. Patients with Hepatitis B provided information to us through the WHO Quality of Life questionnaire. Data analysis conducted in this study was a chi-square test and a multivariate logistic regression model was used to calculate the odds ratios (OR). This study involved 31 people with varying quality of life. The average age range for good quality of life was 33 years, with 61.9% of patients being Javanese and 38.1% being Madurese. 70% of very good quality of life patients were Javanese, while 30% were Madurese. High school education was the most common, with 52.4% of patients having a good quality of life. Most patients worked as housewives, with 90.5% and 9.5% as factory employees. Hepatitis B control history was also a significant factor, with 57.1% of patients having never had it. Pregnancy status was 81% of patients with good quality of life, while 90% had no other diseases. Housewives with hepatitis B had a better quality of life than the others (P = 0.043). However, we could not find any association between age, ethnicity, education background, treatment, current pregnancy, and have other disease with quality of life (P = 0.645, P = 0.218, P = 0.417, P = 0.339, P = 0.133 and P = 0.419, respectively). This study reveals a significant relationship between occupation and the quality of life of hepatitis B patients, highlighting the importance of health-related quality of life in evaluating treatment and prognosis.